2017
DOI: 10.3991/ijim.v11i1.6295
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Unicast Routing Protocols in MANETs – Current State and Future Prospects

Abstract: Abstract-Mobile Ad hoc Networks (MANETs) are considered as a reunion of wireless mobile devices (nodes) that form a temporary wireless network. In order to facilitate communication in MANET, every node has to participate in the routing process. Reaching an optimal route is a fundamental task in MANET, because routes are multi-hoped and susceptible. Several routing protocols exist and can be categorized to; topology-based and position-based routing protocols. However, the efficiency of these protocols in highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Other researchers in [24] proposed a new method of channel selection in multi-radio multi-channel WMNs to improve the user performance in downlink direction of Internet traffic. However, the cross-layer method used in the literature [12][13][14][15][16][17], [25] and [26] does not consider the development of IEEE 802.11n/ac MAC and PHY in determining the choice of data rate, nor the best route to produce optimal throughput in IEEE 802.11s WMNs.…”
Section: Related Workmentioning
confidence: 99%
“…Other researchers in [24] proposed a new method of channel selection in multi-radio multi-channel WMNs to improve the user performance in downlink direction of Internet traffic. However, the cross-layer method used in the literature [12][13][14][15][16][17], [25] and [26] does not consider the development of IEEE 802.11n/ac MAC and PHY in determining the choice of data rate, nor the best route to produce optimal throughput in IEEE 802.11s WMNs.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, many studies have been done to improve availability and reliability in MANET [2,5]. Through the related studies [6][7][8][9][10][11][12][13][14][15][16][17][18][19][21][22][23][24][25] showed that how to use mobile agent technology with the intention of improving the performance of MANET becomes an increasingly exciting research topic.…”
Section: Introductionmentioning
confidence: 99%
“…Routing protocols are particularly important in improving network performance. Moreover, the performance of MANETs is generally quite low and depends on its size, communication model and radio communication environment [2,[5][6]14]. Therefore, designing high-performance routing protocols for MANETs is a significant challenge and is an urgent research direction.…”
Section: Introductionmentioning
confidence: 99%